Perceived Risk and the Adoption of Tax E-Filing - Che Azmi, A.A.; Kamarulzaman, Y.; Hamid, N.H.A. (IDOSI Publications, 2012)
Many countries have introduced e-filing of tax returns to help citizens fulfill their responsibilities toward the government. However, despite the presence of such e-services, researchers argue e-filing of taxes is not popular among the public, especially in developing countries like Malaysia, because of the high perceived risk associated with the service. The lack of coordinated efforts on the part of the service provider to counter individual perceptions of risk further discourages the adoption of the tax e-filing service. The paper uses the technology acceptance model to understand how perceived risk and its facets influence the adoption behavior of consumers. By analyzing data from 249 Malaysian taxpayers, the authors found that facets of perceived risk have a positive relationship with the adoption of tax e-filing whereas perceived ease of use of the system does not have a positive relationship with the adoption of tax e-filing. The model suggests that different risk facets may influence the adoption of tax e-filing and perceived usefulness of the system differently.